MEDIA KOSAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA SISWA SEKOLAH DASAR - cahya, niluh suryaning (STKIP PGRI SUMENEP, 2024)
Critical thinking skills are indispensable thinking skills in helping students solve everyday problems. Some of the criteria for critical thinking are being able to analyze arguments, statements or evidence, compiling a conclusion based on deductive reasoning, assessing and evaluating and being able to make problem solving. The purpose of this study is to develop the Science Box (KOSAN) media for students' critical thinking skills on energy materials and their changes in grade 3. The type of research used is Research and Development (R&D). The model that researchers use in this development is ADDIE (analyze, design, development, implement, evaluate). The instruments used in this study were questionnaires and tests. The subjects of this research were carried out by validators (media expert lecturers, materials, languages, 3 class teachers, 1 practitioner expert teacher, and students). The instruments used in this study were questionnaires and tests. The subjects of this research were carried out by validators (media expert lecturers, materials, languages, 3 class teachers, 1 practitioner expert teacher, and students). Researchers conducted research at SD Negeri 2 Karanganyar, SD Negeri 2 Wonorejo and SD Negeri 3 Sukorejo with a total number of students of 31 students. . The results obtained from media experts are at a percentage of 90%, material experts 89%, linguists 92% and ahlli practitioners by 94%. From these data, the media can be said to be valid with the analysis of the data obtained, there is a significant difference from before and after using the media. Evidenced by the results of the Paired test sample t-test showed a sig value of < 0.05, then Ho was rejected.